2015
DOI: 10.1380/ejssnt.2015.135
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Friction of Nanoscale Sliding on a C<sub>60 </sub>Deposited Film

Abstract: We measured the frictional behavior acting on C60 films at a small normal load as a function of oscillation amplitude using a MHz-range quartz crystal resonator and an optical AFM cantilever. The frictional behavior for C60 films varies by the amplitude: For the amplitudes smaller than the C-C bond length of the C60 molecule, the dynamic frictional force is directly proportional to the amplitude, while it becomes almost constant for larger amplitudes. Although the observation is in qualitatively the same manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This may be attributed to two factors according to the structural properties of fullerene molecules. On the one hand, fullerene molecules could act as molecular bearings during the rubbing process. Miura et al have also proposed a stick–slip rolling model with a step rotation of a C 60 molecule to reveal the detailed mechanism. On this basis, the lubrication mechanism model is presented as shown in Figure b,c.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to two factors according to the structural properties of fullerene molecules. On the one hand, fullerene molecules could act as molecular bearings during the rubbing process. Miura et al have also proposed a stick–slip rolling model with a step rotation of a C 60 molecule to reveal the detailed mechanism. On this basis, the lubrication mechanism model is presented as shown in Figure b,c.…”
Section: Discussionmentioning
confidence: 99%
“…However, so few of these measurements exist in the literature that there has been virtually no experimental support for this theoretically supportable hypothesis. This is important because a variety of mechanical systems have been used to implement QCM-based friction measurements of solid-on-solid contacts, including atomic force microscopes, ,,, scanning tunneling microscopes, , nanoindentation, , surface forces apparatus, and dedicated normal force or displacement transducers to engage a sphere with the QCM surface. ,,, Another approach is to attach three spheres to a weighted plate and set the assembly onto the QCM. ,,, We note that most of these prior experiments have studied the partial slip regime, although several different groups have observed the transition from partial to full slip. ,, Only two previous studies have reported quantitative measurements of kinetic friction in full slip conditions using the energy dissipation technique used here. , The results of this study experimentally support the hypothesis that QCM-based friction measurements are insensitive to the mechanical attributes of the measurement system. This outcome suggests (1) that QCM-based friction results can be safely compared between studies and (2) that the QCM-based approach can be integrated with any existing spring-based instrument (e.g., AFM or microtribometer).…”
Section: Discussionmentioning
confidence: 99%
“…However, so few of these measurements exist in the literature that there has been virtually no experimental support for this theoretically supportable hypothesis. This is important because a variety of mechanical systems have been used to implement QCM-based friction measurements of solid-onsolid contacts, including atomic force microscopes, 31,32,39,40 scanning tunneling microscopes, 35,38 nanoindentation, 27,41 surface forces apparatus, 42 and dedicated normal force or displacement transducers to engage a sphere with the QCM surface. 28,30,34,37 Another approach is to attach three spheres to a weighted plate and set the assembly onto the QCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, lubricants are being developed to reduce the friction losses in these systems. Lubricants can be categorized as solid lubricants [2][3][4], semisolid lubricants [5], and liquid lubricants [6][7][8]. Liquid lubricants under boundary lubrication reduce friction and wear by forming an adsorption and reaction layer at the friction interface.…”
Section: Introductionmentioning
confidence: 99%